Two-dimensional lanthanide coordination polymer nanosheets for detection of FOX-7. Issue 4 (13th December 2019) - Singha Mahapatra, Tufan; Dey, Ananta; Singh, Harwinder; Hossain, Sk Saddam; Mandal, Amal Kumar; Das, Amitava
Abstract : A new class of luminescent lanthanide 2D nanosheets for detection of FOX-7. Abstract : Despite the recent surge of interest in two-dimensional (2D) inorganic nanosheets derived from photoactive coordination polymers of lanthanide ions having interesting optical properties, research in this area is still in its infancy. Luminescent lanthanide ions, Eu(iii ) or/and Tb(iii ), as well as a bis-terpyridine ligand (L), were used in this study as the building blocks for the synthesis of the archetypical layered structure of coordination polymers (CPs) (L·Eu/L·Tb). 2D-nanosheets were obtained through exfoliation of the layered precursor of CPs in a suitable solvent system following a sonication-assisted strategy. These nanosheets exhibit lateral sizes on the micrometer scale (0.3–1 μm) and an ultrathin thickness of 2–6.5 nm. 1, 1-Diamino-2, 2-dinitroethene or FOX-7 is an insensitive high explosive; in a binder mixture, it exhibits a slightly superior detonation velocity of 8870 m s −1 in comparison to RDX. The insensitive nature of FOX-7 makes it a key component for the development of low vulnerable high explosive compositions for further application in weaponry. The growing demand for FOX-7, for use as a suitable replacement of conventional explosives, is of serious concern to human security. Achieving rapid and efficient detection of this unexplored explosive is a challenging task. In the present study, the developed luminescent nanosheets were used for the first time for micromolar level detection of FOX-7 both in solution and in the solid state. A visually distinct color change of the nanosheets from red (L·Eu) and green (L·Tb) to colorless was witnessed upon UV light irradiation during the detection process. Notably, the solid-state detection technique could be exploited for developing a commercial spray kit for quick onsite screening of this important explosive.